2014
DOI: 10.1097/cin.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Use of Electronic Clinical Tracking Systems in Advanced Practice Registered Nurse Education

Abstract: Over the past decade, the federal government has mandated healthcare providers to incorporate electronic health records into practice by 2015. This technological update in healthcare documentation has generated a need for advanced practice RN programs to incorporate information technology into education. The National Organization of Nurse Practitioner Faculties created core competencies to guide program standards for advanced practice RN education. One core competency is Technology and Information Literacy. Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The literature reports that celectronic tracking systems are superior to paper-based tracking systems. [1][2][3] Thus, the purpose of this perspective article is not to compare paperbased vs electronic tracking systems, but rather to demonstrate an innovative approach utilizing available resources, as well as a streamlined concept employing an electronic tracking system at a low to no costs alternative.…”
Section: Challenges With a Paper-based Tracking Systemmentioning
confidence: 99%
“…The literature reports that celectronic tracking systems are superior to paper-based tracking systems. [1][2][3] Thus, the purpose of this perspective article is not to compare paperbased vs electronic tracking systems, but rather to demonstrate an innovative approach utilizing available resources, as well as a streamlined concept employing an electronic tracking system at a low to no costs alternative.…”
Section: Challenges With a Paper-based Tracking Systemmentioning
confidence: 99%
“…The authors address the implications of the research in relation to evidence-based practice and information literacy. Branstetter, M.L., Smith, L.S. and Brooks, A.F.…”
Section: Alvarezmentioning
confidence: 99%
“…Publications oriented toward medical libraries include articles addressing health literacy and information skills among people with difficult health conditions (Lloyd et al, 2014;Spring, 2014), as well as other specific populations (Babalola et al, 2014;Smith et al, 2014). Several publications discuss the integration of various technologies, such as online evidence-based practice tutorials (Foster et al, 2014), clinical tracking systems (Branstetter et al, 2014) and mobile apps (Airth-Kindree and Vandenbark, 2014;Stokes et al, 2014), into health sciences education. In addition, as in years past, many articles consider information literacy pedagogy and/or information technology training for students in nursing (McCulley and Jones, 2014), public health (Pannabecker et al, 2014) and other fields.…”
mentioning
confidence: 99%
“…In a similar vein, an integrative review by Branstetter et al. 111 concluded that electronic clinical tracking systems are increasingly being utilised in advanced practice registered nurse education.…”
Section: Introductionmentioning
confidence: 99%